Myocarditis and cardiomyopathy. (May 2018) - Buggey, Jonathan; ElAmm, Chantal A.
Abstract : Purpose of review: The aim of this study is to summarize the literature describing the pathogenesis, diagnosis and management of cardiomyopathy related to myocarditis. Recent findings: Myocarditis has a variety of causes and a heterogeneous clinical presentation with potentially life-threatening complications. About one-third of patients will develop a dilated cardiomyopathy and the pathogenesis is a multiphase, mutlicompartment process that involves immune activation, including innate immune system triggered proinflammatory cytokines and autoantibodies. In recent years, diagnosis has been aided by advancements in cardiac MRI, and in particular T1 and T2 mapping sequences. In certain clinical situations, endomyocardial biopsy (EMB) should be performed, with consideration of left ventricular sampling, for an accurate diagnosis that may aid treatment and prognostication. Summary: Although overall myocarditis accounts for a minority of cardiomyopathy and heart failure presentations, the clinical presentation is variable and the pathophysiology of myocardial damage is unique. Cardiac MRI has significantly improved diagnostic abilities, but endomyocardial biopsy remains the gold standard. However, current treatment strategies are still focused on routine heart failure pharmacotherapies and supportive care or cardiac transplantation/mechanical support for those with end-stage heart failure.